EXAMINATION OF THE OWNERSHIP OF INTELLECTUAL PROPERTY RIGHTS IN ARTIFICIAL INTELLIGENCE GENERATED DOCUMENTS. - Damilola Seun Adesanya; Mujeeb Ademola Imran (ABUAD Law Journal, 2024)
The modern-day reality is that the world has seen unprecedented evolution in information technology and artificial intelligence. In the opinion of theorist of technological convergence, the acceptance of information technology has become necessary as almost every facet of life revolves around it. In fact, technological determinism posits that advanced technology is taking over the entire landscape of human existence, including learning and research. This is buttressed by the evolution of Artificial Intelligence (AI) tools that aid in research, writing and referencing. The evolution of these AI tools necessitates a conversation about the ownership and protection of Intellectual Property Rights (IPRs) in materials generated using these AI tools. It has also become important to define what amounts to infringements of these IPRs, at what point an infringement could be stated to have occurred and who would be held liable for such infringements. This paper adopts the doctrinal research methodology to analyse primary and secondary sources of data in order to determine the issues of ownership and protection of IPRs emanating from the use of AI tools for research. It submits that the use of AI tools in research presents some fresh problems for Intellectual Property (IP) protection and enforcement which should be addressed through making amendment to existing IP laws in Nigeria. The study concludes by making recommendations on how to fortify our existing legal regimes and weed out loopholes that can be exploited to successfully infringe on the rights of AI generated IPRs holders.